Case study method in terms of activity-competent approach to teaching social workers - Плахова, О. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article substantiates the relevance of the implementation of the case study method in the educational process of social workers training, as well as explores the methodological features of its development and implementation in the field of social work. The article defines the concept of “case study”, examines the historical aspect of its development, provides an overview of various classifications, offers recommendations on the methodological support of the educational process using the case study method. Article examines intercommunication of “activity” and “competence” approaches in organization of educational process, it assists to get practical experience of future specialists. For this reason, an educational process should be filled with teaching forms and methods to promote forming the practical abilities and skills. The method of case study plays the special role among of them. The first attempts to use this method were observed in practice of charitable organizations at the end of XIX century in the USA for social workers teaching. With a lack of textbooks and methodical manuals for professional training of specialists, the case study became the primary teaching method that included fixation, discussion, diagnostics of the real case of client. With the passing of the time, after development of the plenty specialized social work literature, case study does not lose the actuality and importance in the American teaching process. The article observes different case study classifications offered in scientific literature, namely: classifications of L. Kottrell, R. Stacke, L. Stenhaus, R. Yin. The typology proposed by R. Yin includes analytical (explanatory) and descriptive type of case study. It should be drawn upon and considered as the most suitable for an educational process within the “activity” and “competence” approach. The attention is focused on requirements to teacher qualifications, qualitative and quantitative structure of students group.